Comparative analysis of optical aberrations, anatomical and optical parameters of the cornea in glaucoma surgery - V. V. Neroev; A. A-G. Aliev; M. M. Nurudinov (Российский офтальмологический журнал)
Purpose. A combined comparative study of the impact of antiglaucomatous surgeries on the anatomical and optical parameters of the cornea.Materials and methods. The study involved 38 patients (38 eyes) aged 43 to 75 with primary open-angle glaucoma (POAG), which were divided into 2 groups. Patients of group I (15 eyes) underwent classical deep sclerectomy (DSE), while those of group II (23 eyes), had non-penetrating deep sclerectomy (NDSE). All patients underwent a comprehensive examination before and after surgery, including precision visometry, corneal topography, OCT pachymetry.Results. Group I revealed a significant change in the parameters on the 3rd day after the surgery; in particular, the average value of corneal astigmatism increased from -0.93 D to -3.62 D, the curvature radius of the cornea in the vertical meridian increased from 7.56 ± 0.07 mm to 8.34 ± 0.04 mm, the thickness of the central cornea changed from 514.5 ± 0.04 μm to 520.6 ± 0.06 μm. In group II, the corneal astigmatism increased from -0.86 D to -2.75 D, and the curvature radius of the cornea in the vertical meridian changed from 7.72 ± 0.05 mm to 8.12 ± 0.03 mm, the central thickness of the cornea increased from 515.4 ± 0.04 to 516.8 ± 0.12 μm.Conclusion. The degree of surgically induced changes of anatomic and optical parameters of the cornea in POAG patients depended on the amount of intervention: NDSE has a lesser effect on these parameters than classical DSE.